A Case Study of Athletes' Physical Condition Before the DKI Jakarta Pelatda for Water Ski and Wakeboard - Uzizatun Maslikah; Fahmy Fachrezzy; Masnur Ali; Endy Safadilla; Haris Nugroho; Mansur Jauhari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The descriptive method employs a qualitative sort of research methodology. 16 water ski and wakeboard athletes 9 men and 7 women made up the study's population and samples. Tests and measurements are used in data gathering techniques, including the measuring of weight using scales. physical condition tests: flexibility using the sit-and-reach test, agility using the shuttle run test, muscle endurance using sit-ups and push-ups, limb explosive power performing vertical jump tests, arm power testing with the use of throw medicine balls, test balance using the standing stroke, an aerobic using a 300 meter sprint, and endurance performing the bleep test. Overall data analysis utilizing Microsoft Excel 2019 and quantitative descriptive analysis methodologies According to the study's findings, physical fitness is a crucial aspect in determining an athlete's success, especially for DKI Jakarta Provincial Water Ski and Wakeboard Athletes who are training to become DKI Jakarta Regional Athletes for PON 2024. To improve athlete performance, more research must be done on environmental influences, psychological issues, athlete psychology, and related topics.